Association between the menstrual cycle and anterior cruciate ligament injuries in female athletes - Wojtys, E. M.; Huston, L. J.; Lindenfeld, T. N.; Hewett, T. E.; Greenfield, M. L. V. H. (The American Journal of Sports Medicine, 1998)
Anterior cruciate ligament injury rates are four to eight times higher in women than in men. Because of estrogen's direct effect on collagen metabolism and behavior and because neuromuscular performance varies during the menstrual cycle, it is logical to question the menstrual cycle's effect on knee injury rates. Of 40 consecutive female athletes with acute anterior cruciate ligament injuries (less than 3 months), 28 (average age, 23 ± 11 years) met the study criteria of regular menstrual periods and noncontact injury. Details concerning mechanism of injury, menstrual cycle, contraceptive use, and previous injury history were collected. A chi-square test was used to compute observed and expected frequencies of anterior cruciate ligament injury based on three different phases of the menstrual cycle: follicular (days 1 to 9), ovulatory (days 10 to 14), and luteal (day 15 to end of cycle). A significant statistical association was found between the stage of the menstrual cycle and the likelihood for an anterior cruciate ligament injury (P = 0.03). In particular, there were more injuries than expected in the ovulatory phase of the cycle. In contrast, significantly less injuries occurred in the follicular phase. These hormones may be a factor in the knee ligament injury dilemma in women.